THE ROLE OF NINIK MAMAK IN KENAGORIAN GUNUNG MALELO KOTO KAMPAR HULU REGION REGENCY OF KAMPAR - Padhol, Hairi Padhol Hairi; Saiman, Marwoto Saiman Marwoto; ', Bunari ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: Ninik Mamak is the custom leader or the leader of tribe in KenagorianGunung Malelo who have important role in every tribe according to the role of customused in Kenagorian Gunung Malelo. The role Ninik Mamak can control the behavior ofniece and nephew and also village government policy. The purpose of this research is toknow how far the role of Ninik Mamak in Kenagorian Gunung Malelo. The researchinterview all of Ninik Mamak in Kenagorian Gunung Malelo that count nine personsand also to get the opinion of another persons (villagers leader) that connecting withresearch. The method that used in this research is historic research method. Directinterview to the respondent and than its made in sentences form according to the resultof interview. The result of research shown that the role of Ninik Mamak in KenagorianGunung Malelo suittble with them function and duty in low of custum used.Result of this research indicate that Ninik Mamak in Kenagorian Gunung Malelohave each role. This role divided into two form that is duty and function from eachevery the Ninik Mamak. Then in this role Ninik Mamak also have certain boundaries inthe duty and function. More circumstantial again also made balance to with people careabout role this Ninik Mamak in Kenagorian Gunung Malelo.Key words : The role, Ninik Mamak.